AN ANALYSIS OF GENDER ACCESS TO UNIVERSITY, SCIENCE, TECHNOLOGY AND MATHEMATICS EDUCATION: A STUDY OF ADMISSION EXERCISES OF USMANU DANFODIYO UNIVERSITY, SOKOTO - Auwal, Yusha’u Muhd; Wushishi, D. I.; Umar, Shehu (Sokoto Educational Review, 2020)
The study analyses gender access to university, science, technology and mathematics education (STM) for the 2005/2006 to 2007/2008 sessions admission of Usmanu Danfodiyo University, Sokoto. Content Analysis Research Design Approach (CARDA) was adopted. Four research questions were addressed; from which two hypothesis were tested using Analysis of Variance statistic (ANOVA) with the aid of computer statistical package for the social sciences (SPSS). It was found that wide gender gap exists in terms of both access to University education and STM education. There are equally significant differences in these gender gaps. The government policy on 60:40 ratios for admission in favour of sciences is not being met. So, it was suggested that the factors identified as inhibiting gender access to education could be overcome if the government could improve access for female gender by seriously reinvigorating, emphasizing and strengthening school science through committed financial provision to address real issues at the primary, secondary and tertiary institutions.